2021
DOI: 10.1177/14687968211005104
|View full text |Cite
|
Sign up to set email alerts
|

(C)overt linguistic racism: Eastern-European background immigrant women in the Australian workplace

Abstract: Linguistic racism explores the varied ideologies that may generate and endorse monolingual, native, and normative language practices, while reinforcing the discrimination and injustice directed towards language users whose language and communicative repertoires are not necessarily perceived as standard and normal. This article, thus, investigates linguistic racism, as a form of existing, but newly defined, racism against unconventional ethnic language practices experienced by Eastern-European immigrant women i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 98 publications
0
23
0
Order By: Relevance
“…Moreover, the emphases of these concepts are highly ideologised, pre‐fixing particular language users’ practices as nameable categories under broader categories of the nation‐state, race, and/or ethnicity (Canagarajah & Dovchin, 2019; Li & Hua, 2013; Tankosić, 2020). Overall, these concepts still operate within the framework of monolingual ideologies since they support the notion that codes still come from and move towards different language systems – these distinct linguistic codes are then rarely considered to belong to the appropriated language but to the appropriating one (Canagarajah, 2013; Tankosić & Dovchin, 2021).…”
Section: The Relocalisation Of Englishmentioning
confidence: 99%
“…Moreover, the emphases of these concepts are highly ideologised, pre‐fixing particular language users’ practices as nameable categories under broader categories of the nation‐state, race, and/or ethnicity (Canagarajah & Dovchin, 2019; Li & Hua, 2013; Tankosić, 2020). Overall, these concepts still operate within the framework of monolingual ideologies since they support the notion that codes still come from and move towards different language systems – these distinct linguistic codes are then rarely considered to belong to the appropriated language but to the appropriating one (Canagarajah, 2013; Tankosić & Dovchin, 2021).…”
Section: The Relocalisation Of Englishmentioning
confidence: 99%
“…ESL-migrants’ linguistic features often reveal their ethno-cultural identities, which eventually leads to social comparisons, ‘in which the in-group [dominant society] is perceived as better than that of the out-group [ESL]’ (Bhatia, 2018, p. 423). Therefore, linguistic subordination often co-occurs with linguistic racism , which, in addition to language-based discrimination, also discriminates against minorities’ ethno-racial, social, and cultural background (Tankosić & Dovchin, 2021). In other words, linguistic subordination becomes, not exclusively but predominantly, directed at marginalised groups, whose linguistic repertoire uncovers their identity, hence simultaneously making them victims of linguistic racism.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research, which evaluated the level of different accent comprehensibility, showed that mixed accent groups achieved a higher intelligibility than dominant speakers (Smith & Nelson, 2006), while it is the prejudice of biographical accents that prevents dominant speakers from actually hearing what others are saying (Lippi-Green, 1994). Biographical accents can often have a negative impact on credibility and employability (Lee, 2018), and cause mocking and social exclusion (Dovchin, 2019b; Tankosić & Dovchin, 2021). ESL-migrants in Australian institutional and noninstitutional settings are often judged, stigmatised, and bullied for speaking broken and inadequate English (Dovchin, 2019a, 2019b, 2020a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations